2016
DOI: 10.1051/matecconf/20178802001
|View full text |Cite
|
Sign up to set email alerts
|

A Facile and Green Synthetic Route for Preparation of Heterostructure Fe3O4@Au Nanocomposites

Abstract: Abstract. Magnetic nanoparticles offer many exciting opportunities in biology and biomedicine, such as magnetic resonance imaging, magnetic hyperthermia therapy, biomedical diagnosis. The synthesis of multifunctional magnetic nanocomposites that possess watersolubility, magnetic properties and optical stability by a green method at room temperature in aqueous phase is still an unmet need. Here, we developed a simple and green method for preparing Fe3O4@Au integrated the super-paramagnetic and optical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Eliminating the use of organic solvents throughout the synthetic process and using only biocompatible, non-toxic materials and reagents streamlines the synthesis for biological purposes. An aqueous synthetic method and biocompatible polymer was utilised in the synthesis of heterostructured Fe3O4@PVP@Au nanocomposites [24]. In this synthesis, PVP (polyvinylpyrrolidone) polymer was used to stabilise the Fe3O4 nanoparticles, and also to form a homogenous layer surrounding them that has a negative charge.…”
Section: Synthesis Of Core/polymer/shell Magnetic-plasmonic Nanopartimentioning
confidence: 99%
See 1 more Smart Citation
“…Eliminating the use of organic solvents throughout the synthetic process and using only biocompatible, non-toxic materials and reagents streamlines the synthesis for biological purposes. An aqueous synthetic method and biocompatible polymer was utilised in the synthesis of heterostructured Fe3O4@PVP@Au nanocomposites [24]. In this synthesis, PVP (polyvinylpyrrolidone) polymer was used to stabilise the Fe3O4 nanoparticles, and also to form a homogenous layer surrounding them that has a negative charge.…”
Section: Synthesis Of Core/polymer/shell Magnetic-plasmonic Nanopartimentioning
confidence: 99%
“…Hydroxylamine has frequently been utilised as a seeding and reducing agent in a number of cases for coating of magnetic nanoparticles with a plasmonic shell [24,27,28]. For example, Fantechi et al first synthesised ultrasmall Fe3O4 NPs using Massart's coprecipitation; then, hydroxylamine was used as a seeding agent for the gold NPs ( Figure 2) [28].…”
Section: Synthesis Of Magnetic-plasmonic Nanoparticles Without Intermmentioning
confidence: 99%
“…While numerous studies have demonstrated the production of hybrid gold-based nanoparticles, a reliable and predictable synthetic strategy that provides reproducibility has not been realized. There are two main approaches in the literature to synthesize these materials: In the first case, gold seeds with a diameter of 1-3 nm are prepared by the reduction with borohydride [27] or sodium citrate [28]. Then, the obtained seeds are added to magnetic particles.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies have demonstrated the production of hybrid gold-based nanoparticles, a reliable and predictable synthetic strategy that provides reproducibility has not been realized. There are two main approaches in the literature to synthesize these materials: In the first case, gold seeds with a diameter 1-3 nm are prepared by the reduction with borohydride [23] or sodium citrate [24]. Then, the obtained seeds are added to magnetic particles.…”
Section: Introductionmentioning
confidence: 99%